ANALYSIS OF THE INFLUENCE OF WORKING CAPITAL ASSETS AND FIXED ASSETS ON COMPANY PROFITABILITY (Study on Construction Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period) - Quatrinasa, Daru; Muid, Dul (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of working capital and fixed assets on company profits from construction companies listed on the Indonesia Stock Exchange in 2019-2021. This study aims to find empirical evidence regarding working capital. (Working Capital) and fixed assets (Fixed Assets) on company profits or profitability, so that they can provide views to company management or to investors and stakeholders to find out relevant accounting information regarding company profits or profitability in financial reports.The research method used in this study was a quantitative approach with a population of 62 construction companies and 22 construction companies were taken as research samples. The data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) which is used as the research sample. The analysis technique used is multiple linear regression.The results of testing the hypothesis stated that the working capital variable and the correlation between working capital and fixed assets had a positive effect on company profits or profitability, while this study found that fixed assets (Fixed Assets) had a negative effect on company profits or profitability.